Instrument building as a tool for the revitalisation and revaluing of traditional music transmission: An investigation in Tshandama and Mbahe in Venda, South Africa - Makhanza, Joseph (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
This study stems from my experiences as a child who grew up playing herd boys' musical instruments from Venda, such as the tshipotoliyo (ocarina), and tshitiringo (flute). Importantly it also builds on my time working at the International Library of African Music (ILAM,) where the aforementioned instruments, as well as the dende (musical bow) and tshizambi (Vhavenda and Vatsonga mouth bow), are displayed in transparent glass cubicles with a note, "Do not touch, they are fragile" . This phrase is painfully apt because, as a musician, I have observed a decline in the availability and performance of these musical instruments. The truth is that, other than at ILAM, these instruments are hardly in circulation, let alone being performed. This fact ignited my interest in relearning some of the musical instruments I used to play and make while herding cows in Giyani. In the context of trends such as modernisation, rural"“urban migration, and globalisation, I document my experiences as a musical-instrument maker, teacher, and performer in revitalising dende, tshipotoliyo, tshitiringo, and tshizambi through classroom practice, using Rhodes music students, instrument-making workshops, performances, and community collaborations as inspiration. I propose the development of crafting skills as a medium for revitalising and sustaining these musical instruments which serve as important identity markers of the Vhavenda people.
Keywords: Instrument making; Ecomusicology -- South Africa Venda; Venda (African people) Music; Group identity -- South Africa Venda; Musical instruments -- South Africa Venda; Environmental awareness